Alteration in Inflammatory Responses and Cytochrome P450 Expression of Porcine Jejunal Cells by Drinking Water Supplements - Palócz, Orsolya; Szita, Géza; Csikó, György (Mediators of Inflammation, 2019)
The intestinal epithelium is the first determining barrier to the drugs administered per os. Cytochrome P450 (CYP) enzymes are substantial in the initial step of xenobiotic metabolism; therefore, intestinal CYP enzyme activities could be an important influencing factor of the oral utilization of xenobiotic substances. In this study, the effect of four drinking water supplements on CYP mRNA levels of porcine intestinal epithelial cells was examined. Further goal of the study is to describe the effect of these feed additives on the proinflammatory response of the LPS-treated enterocytes. The nontransformed porcine intestinal epithelial cells (IPEC-J2) were grown on six-well polyester membrane inserts. Cell cultures were treated with LPS (10 μg/ml), β-glucan (5 and 50 μg/ml), sanguinarine-containing additive (5 and 50 μg/ml), drinking water acidifier (0.1 and 1 μl/ml), and fulvic acid (25 and 250 μg/ml) for 1 hour. Cells were washed with culture medium and incubated for additional 1 h before total RNA isolation. IL-6, IL-8, TNF-α, HSP70, CYP1A1, CYP1A2, and CYP3A29 mRNA levels were measured. The LPS treatment upregulated the gene expression of IL-8 and TNF-α. The relative gene expression of IL-6 remained unchanged and TNF-α and HSP70 were downregulated after the treatment with each feed additive. CYP1A1 and CYP1A2 expressions increased after sanguinarine-containing solution, fulvic acid, and drinking water acidifier treatment. None of the treatments changed the gene expression of CYP3A29, responsible for the metabolism of the majority of drug substances used in swine industry. The feed additive substances inhibited the expression of proinflammatory mediators HSP70 and TNF-α; however, β-glucan and fulvic acid elevated the production of the chemokine IL-8 mRNA in endotoxin-treated enterocytes. All acidic supplements increased the expression of CYP1A1 gene; their constituents may serve as a ligand of CYP1A1 nuclear receptors.